Kinetic analysis of the influenza A virus HA/NA balance reveals contribution of NA to virus-receptor binding and NA-dependent rolling on receptor-containing surfaces - Guo, Hongbo; Rabouw, Huib; Slomp, Anne; Dai, Meiling; van der Vegt, Floor; van Lent, Jan W. M.; McBride, Ryan; Paulson, James C.; de Groot, Raoul J.; van Kuppeveld, Frank J. M.; de Vries, Erik; de Haan, Cornelis A. M. (PLoS pathogens, 2018)
Interactions of influenza A virus (IAV) with sialic acid (SIA) receptors determine viral fitness and host tropism. Binding to mucus decoy receptors and receptors on epithelial host cells is determined by a receptor-binding hemagglutinin (HA), a receptor-destroying neuraminidase (NA) and a complex in vivo receptor-repertoire. The crucial but poorly understood dynamics of these multivalent virus-receptor interactions cannot be properly analyzed using equilibrium binding models and endpoint binding assays. In this study, the use of biolayer interferometric analysis revealed the virtually irreversible nature of IAV binding to surfaces coated with synthetic sialosides or engineered sialoglycoproteins in the absence of NA activity. In addition to HA, NA was shown to be able to contribute to the initial binding rate while catalytically active. Virus-receptor binding in turn contributed to receptor cleavage by NA. Multiple low-affinity HA-SIA interactions resulted in overall extremely high avidity but also permitted a dynamic binding mode, in which NA activity was driving rolling of virus particles over the receptor-surface. Virus dissociation only took place after receptor density of the complete receptor-surface was sufficiently decreased due to NA activity of rolling IAV particles. The results indicate that in vivo IAV particles, after landing on the mucus layer, reside continuously in a receptor-bound state while rolling through the mucus layer and over epithelial cell surfaces driven by the HA-NA-receptor balance. Quantitative BLI analysis enabled functional examination of this balance which governs this dynamic and motile interaction that is expected to be crucial for penetration of the mucus layer and subsequent infection of cells by IAV but likely also by other enveloped viruses carrying a receptor-destroying enzyme in addition to a receptor-binding protein.